Pancho Villa e a Revolução Mexicana - Rampinelli, Waldir José (Diálogos Latinoamericanos, 2007)
México is preparing for the celebration of the 100th anniversary of the Revolution. It was the first great social revolution of the 20th century in Latin America. More than one million people out of a population of 15 million died but many great victories were won, for instance with regard to agrarian reform, the writing of a democratic constitution and the making of a capitalist State. Francisco Villa was the Revolution leader who commanded a professional army in the north of the country. During the revolution he was feared, and long after his death was considered a bandit. However, from the 1970s onwards this view changed as it was claimed that he had been a visionary leader. Paco Ignacio Taibo presents three significant periods of Villa's life during the Mexican Revolution: 1) 1911-1912: Pancho Villa allies with I. Madero to overthrow the dictator Porfírio Diaz. 2) 1913-1915: Villa allies with Álvaro Obregón to defend social changes in the country. 3) 1916-1920: Villa begins a guerrilla warfare strategy to oppose the established bourgeois regime. Nowadays, Villa is perceived as a great leader who contributed radically to the Mexican Revolution.